2009
DOI: 10.22230/cjc.2009v34n4a2122
|View full text |Cite
|
Sign up to set email alerts
|

Urban Mediascapes and Multicultural Flows: Assessing Vancouver’s Communication Infrastructure

Abstract: This article adopts a communication infrastructure model in mapping the flow and meaning of ethnic media in Vancouver and their interaction with local, national, and global conceptions of a public commons. A communication infrastructure consists of a “thick” social network of media and organizations, which create and disseminate everyday conversations and news to any given community. Without the existence of a sustainable communication infrastructure, communities cannot form and function. The intersection of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The priorities identified by ethnic publishers and editors are consistent with the social responsibility theory of journalism, defined by Ahadi and Murray (2009) as local news coverage that aims to "raise intercultural awareness and assist new immigrants with integration" (603). Scholarly research, however, suggests there are significant differences in the extent to which individual ethnic news outlets live up to these goals.…”
Section: The Best Of Intentions: the Role Of Ethnic News Outlets In Ethnic Communitiesmentioning
confidence: 86%
See 2 more Smart Citations
“…The priorities identified by ethnic publishers and editors are consistent with the social responsibility theory of journalism, defined by Ahadi and Murray (2009) as local news coverage that aims to "raise intercultural awareness and assist new immigrants with integration" (603). Scholarly research, however, suggests there are significant differences in the extent to which individual ethnic news outlets live up to these goals.…”
Section: The Best Of Intentions: the Role Of Ethnic News Outlets In Ethnic Communitiesmentioning
confidence: 86%
“…One study of the people who produced ethnocultural publications in Canada (Miller 2006) found that 41% had no business or journalism training. Researchers in British Columbia have suggested that some proprietors of ethnic news operations are in the business more for the money than to provide a voice for the community (Ahadi and Murray 2009). Lam (2010) said that while most of his staff members did not receive formal journalism training in North America, the majority did study journalism in mainland China or Hong Kong and almost all had journalism experience prior to joining Ming Pao.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One survey, for instance, found that 41 per cent of the people producing ethnic news had no business or journalism training (Miller 2006). Researchers in British Columbia identified the belief in some ethnic communities that some publishers are in the business more for the money than to provide a voice for the community (Ahadi and Murray 2009). While most of the journalists at Ming Pao did not study journalism in North America, the majority did receive formal training in mainland China or Hong Kong, and almost all had journalism experience prior to joining the paper (Lam 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The decision by Canada's political class to embrace ethnocultural media highlights the need to understand the role of these news organizations in the political process. Limited research in this area has led scholars to suggest it would be worthwhile “to investigate ethnic media's ‘behaviour’ during election times to better understand the type of issues that get covered, as well as how politicians and policies are addressed in the ethnic media” (Ahadi and Murray, 2009: 605). More generally, Kymlicka (2008) has identified the need for a better understanding of institutional structures, including ethnocultural media, in ethnic and immigrant communities.…”
Section: Introductionmentioning
confidence: 99%